Assessment of optimal condylar position with cone-beam computed tomography in south Indian female population - W S Manjula; Faizal Tajir; R V Murali; S Kishore Kumar; Mohammed Nizam (Wolters Kluwer Medknow Publications, 2015)
Aim: The purpose of this study was to investigate, the condyle-fossa relationship, in clinically asymptomatic orthodontically untreated south Indian female volunteers, by cone-beam computed tomography (CBCT). Materials and Methods: The study population consisted of 13 clinically symptom-free and orthodontically untreated angle's Class I female subjects with the mean age of 18 years (ranges from 17 years to 20 years). The normal disc position of the 13 subjects was confirmed by history, clinical examination and magnetic resonance imaging scan. Then, the images of the temporomandibular joint (TMJ) of the subjects were taken using CBCT to evaluate the optimal condylar position. Posterior joint space (PS), superior joint space (SS) and anterior joint space (AS) were measured, and the values were subjected to statistical analysis. Mean PS, SS and AS of right and left side TMJ's were calculated. Paired samples t-test were used for each measurement to evaluate the average differences between the right and left side for each element of the sample. Results: The mean value of PS, SS and AS of right side TMJ's were 2.1385, 2.2769 and 1.7615, respectively. The mean value of PS, SS and AS of left side TMJ's were 2.1385, 2.5308 and 1.8538, respectively. Statistical analysis with the t-test indicated no significant differences in the AS, SS, or PS values between the right and left side. TMJ's mean PS, SS, and AS measurements were 2.1 mm (standard deviation [SD] ±0.65 mm), 2.4 mm (SD ± 0.58 mm), and 1.8 mm (SD ± 0.52 mm), respectively. The ratios of SS and PS to AS, with AS set to 1.0, were 1.3 and 1.2, respectively. Conclusion: These data from optimal joints might serve as norms for the clinical assessment of condylar position obtained by CBCT.